#### Answer

1. The second term is 4
2. The third term is 0
3. The fourth term is -4
4. The explicit formula is A(n)=8-4(n-1)

#### Work Step by Step

A(1)=8
1. The second term is
A(2)=A(2-1)-4 = A(1)-4 = 8-4 = 4
2. The third term is
A(3)=A(3-1)-4 = A(2)-4 = 4-4 = 0
3. The fourth term is
A(4)=A(4-1)-4 = A(3)-4 = 0-4 = -4
4. The explicit formula is A(n)=8-4(n-1)
Because the sequence is in the form of A(n)=A(1)-d(n-1) and the value of A(1) is 8 and the value of d is -4 as it was derived from the recursive formula and also from the sequence.